The Egyptian Stabilization Experience An Analytical Retrospective - Subramanian, Arvind (International Monetary Fund, 1997)
This paper analyzes the successful Egyptian stabilization experience during the 1990s, focusing on its distinctive features and contrasting them with the recent experiences of other developing countries. The key policy elements were a large fiscal adjustment, use of an exchange rate anchor that has endured for over six years, supported by prudent monetary policies, and early moves to liberalize interest and exchange markets. The outcomes included the avoidance of an output collapse despite the magnitude of fiscal adjustment; avoidance of stresses on the financial system; reversal of endemic dollarization; financial deepening at the expense of the banking system; and maintenance of external viability despite a lackluster export performance